Implementation of Legal Protection for Indonesian Migrant Workers Before Departure by the Regional Government of Indramayu Regency - Lulu Padilah Pratama; Moh. Sigit Gunawan (Ann Publisher, 2026)
Background. The movement of Indonesian people to work abroad as Indonesian Migrant Workers (PMI) is a significant socio-economic phenomenon, especially in Indramayu Regency. However, the position of migrant workers is still vulnerable to human rights violations, even before departure. Method. The empirical juridical method is used in this study, which is a method that examines the provisions in the applicable laws and regulations and relates them to the conditions that occur in the field. Results. The results of the study show that the Indramayu Regency Government has implemented legal protection for Indonesian Migrant Workers (PMI) before departure in accordance with the provisions of the law. However, the implementation is not optimal because there are still many prospective migrant workers who depart through non-procedural routes. The efforts of the Indramayu Regency Regional Government in overcoming obstacles are carried out through increasing socialization and community education, strengthening coordination between the Manpower Office, the Indonesian Migrant Worker Protection Service Center (BP3MI), village governments, Indonesian migrant worker placement companies (P3MI), and law enforcement officials, as well as increasing supervision of the recruitment and placement process of migrant workers. The village government also plays a role in data collection, document verification, and information to prospective migrant workers. Conclusion. The Indramayu Regency Government has implemented legal protection for migrant workers before departure in accordance with applicable regulations, but it is not optimal because there are still non-procedural departures. Efforts made include increasing socialization, coordination, supervision, and the role of the village government in data collection, document verification, and providing information to prospective migrant workers.